Astaxanthin Ameliorated Parvalbumin-Positive Neuron Deficits and Alzheimer’s Disease-Related Pathological Progression in the Hippocampus of AppNL-G-F/NL-G-F Mice - Hongo, Nobuko; Takamura, Yusaku; Nishimaru, Hiroshi; Matsumoto, Jumpei; Tobe, Kazuyuki; Saito, Takashi; Saido, Takaomi C.; Nishijo, Hisao (Frontiers in Pharmacology, 2020)
Growing evidence suggests that oxidative stress due to amyloid β (Aβ) accumulation is involved in Alzheimer’s disease (AD) through the formation of amyloid plaque, which leads to hyperphosphorylation of tau, microglial activation, and cognitive deficits. The dysfunction or phenotypic loss of parvalbumin (PV)-positive neurons has been implicated in cognitive deficits. Astaxanthin is one of carotenoids and known as a highly potent antioxidant. We hypothesized that astaxanthin’s antioxidant effects may prevent the onset of cognitive deficits in AD by preventing AD pathological processes associated with oxidative stress. In the present study, we investigated the effects of astaxanthin intake on the cognitive and pathological progression of AD in a mouse model of AD. The AppNL-G-F/NL-G-F mice were fed with or without astaxanthin from 5-to-6 weeks old, and cognitive functions were evaluand using a Barnes maze test at 6 months old. PV-positive neurons were investigated in the hippocampus. Aβ42 deposits, accumulation of microglia, and phosphorylated tau (pTau) were immunohistochemically analyzed in the hippocampus. The hippocampal anti-oxidative status was also investigated. The Barnes maze test indicated that astaxanthin significantly ameliorated memory deficits. Astaxanthin reduced Aβ42 deposition and pTau-positive areal fraction, while it increased PV-positive neuron density and microglial accumulation per unit fraction of Aβ42 deposition in the hippocampus. Furthermore, astaxanthin increased total glutathione (GSH) levels, although 4-hydroxy-2,3-trans-nonenal (4-HNE) protein adduct levels (oxidative stress marker) remained high in the astaxanthin supplemented mice. The results indicated that astaxanthin ameliorated memory deficits and significantly reversed AD pathological processes (Aβ42 deposition, pTau formation, GSH decrease, and PV-positive neuronal deficits). The elevated GSH levels and resultant recovery of PV-positive neuron density, as well as microglial activation, may prevent these pathological processes.